Heavy metals and yield of cowpea cultivated under composted tannery sludge amendment - Gonçalves, Iuna Carmo Ribeiro; Araújo, Ademir Sergio Ferreira; Nunes, Luís Alfredo Pinheiro Leal; Bezerra, Antônio Aécio Carvalho; Melo, Wanderley José De [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2014)
The study aimed to evaluate the phytoavailability of heavy metals (Cr, Cd, Ni and Pb) concentrations in leaves and grains, and yield of cowpea (Vigna unguiculata L) grown in soil amended with composted tannery sludge (CTS) for two consecutive years. The experiments were carried out in 2009 and 2010 in soil amended with CTS at 0, 5, 10, 20, and 40 Mg ha-1. The CTS amendment rates applied were above 10 Mg ha-1, increased Cr concentrations in cowpea leaves. There were not increases in the heavy metals concentrations in cowpea grains after two years. In 2009, the application of CTS amendment did not promote increase in plant yield. However, in 2010, CTS amendment at 10 and 20 Mg ha-1 increased cowpea yield. The amendment of composted tannery sludge linearly increased linearly the concentration of Cr in the leaves of cowpea after two years. Composted tannery sludge promoted increases in cowpea yield.

O estudo objetivou avaliar a fitodisponibilidade de metais pesados (Cr, Cd, Ni e Pb) em folhas e grãos, e produtividade em caupi (Vigna unguiculata L) em solo após a adição de lodo de curtume compostado (LCC) por dois anos consecutivos. Os experimentos foram realizados em 2009 e 2010 em solo com adição de LCC a doses de 0, 5, 10, 20 e 40 Mg ha-1. A adição de LCC em doses acima de 10 Mg ha-1, por dois anos consecutivos, aumentou a concentração de Cr nas folhas do caupi. Não houve aumento na concentração de metais no grão de caupi após dois anos de aplicação. Em 2009, a aplicação de LCC não aumentou a produtividade da planta. Entretanto, em 2010, o LCC nas doses de 10 e 20 Mg ha-1 aumentou a produtividade do caupi. A aplicação de lodo de curtume compostado aumentou linearmente a concentração de Cr nas folhas do caupi após dois anos. O lodo de curtume compostado promoveu aumento na produtividade de grãos.
Metais pesados e produtividade de caupi cultivado sob aplicações de lodo de curtume compostado
Keywords: Vigna unguiculata; resíduo orgânico; elementos traço; Vigna unguiculata; organic residues; trace elements